Effects of initial spacing on the stand structure and yield of young black locust (Robinia pseudoacacia L.) stands - Rédei, K. (International Journal of Horticultural Science, 2009)
The choice of the right initial spacing of stands is one of the most decisive operations of a successful afforestation. It is even more important in the case of fast growing tree species grown in plantations; it is expressed in their early phase of development and in wood quality. The results of a 5-year long experiment with four treatments will be presented in this paper. They proved the priority of an initial spacing of 1.61.0 m in the majority of quality This treatment has been proved optimal exploitation of growing space by the young trees.